Strategi Komunikasi Pembelajar BIPA Dalam Pengenalan Budaya Bugis Makassar Pada Pembelajaran BIPA Tingkat Dasar - F, Fajriani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Indonesian for foreign speakers (BIPA) is Indonesian language instruction given to foreigners who want to learn Indonesian as a foreign language. The objectives of this research are, (1) Describe the nature of culture, (2) Describe the communication strategies of BIPA learners, and (3) Describe the results of communication strategies in teaching Bugis-Makassar culture in BIPA learning. The method used in this paper is descriptive qualitative. The results of the research show that the communication strategy in teaching Bugis-Makassar Culture in BIPA Learning is related to the human way of life. Therefore, this culture includes three forms which relate to what humans do, what they know or think, and what they make or use to fulfill their life needs.